Rediscovering natural flowering. (October 2018) - McCarthy, Kayla; Davis, Seth
Seasonal control of flowering is a dramatic example of interactions between genes and environment, and is mostly studied in growth chambers. However, switching from natural settings to artificial conditions affects phenotypes. More natural responses in cabinets can be obtained by only modifying a few environmental parameters.